2015
DOI: 10.1016/j.ydbio.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Origin and development of neuropil glia of the Drosophila larval and adult brain: Two distinct glial populations derived from separate progenitors

Abstract: Glia comprise a conspicuous population of non-neuronal cells in vertebrate and invertebrate nervous systems. Drosophila serves as a favorable model to elucidate basic principles of glial biology in vivo. The Drosophila neuropil glia (NPG), subdivided into astrocyte-like (ALG) and ensheathing glia (EG), extend reticular processes which associate with synapses and sheath-like processes which surround neuropil compartments, respectively. In this paper we characterize the development of NPG throughout fly brain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 72 publications
7
85
0
4
Order By: Relevance
“…We have also observed that the astrocytes surrounding the ventral sectors of the antennal lobe also extend branches into the subesophageal zone. This suggests that this particular astrocyte might bridge the function between the antennal lobe and the subesophageal zone, consistent with previous publications that imply a close functional relationship between these two brain areas in the larval brain (Omoto et al, 2015). Finally, we have observed that the size of the cell bodies of astrocytes that branch in the mushroom body are larger than those that branch in the antennal lobe.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have also observed that the astrocytes surrounding the ventral sectors of the antennal lobe also extend branches into the subesophageal zone. This suggests that this particular astrocyte might bridge the function between the antennal lobe and the subesophageal zone, consistent with previous publications that imply a close functional relationship between these two brain areas in the larval brain (Omoto et al, 2015). Finally, we have observed that the size of the cell bodies of astrocytes that branch in the mushroom body are larger than those that branch in the antennal lobe.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, some of those GFP + astrocytes infiltrate not only the antennal lobes, but also the dorsal part of the subesophageal zone (Fig. 6C, arrowhead in middle panel), consistent with previous findings of astrocytes in larval central brain (Omoto et al, 2015). Moreover, we found that the cell body size of the GFP + astrocytes surrounding the mushroom bodies (induced by the MB247 driver) is larger than that of the astrocytes close to the antennal lobes (induced by the Orco driver).…”
Section: Monitoring Interactions Between Glia and Specific Types Of Nsupporting
confidence: 91%
See 1 more Smart Citation
“…Like their mammalian counterparts, Drosophila astrocytes extend processes that infiltrate the synaptic neuropil, and tile with one another to occupy non-overlapping territories (Awasaki et al, 2008;Doherty et al, 2009;Omoto et al, 2015;Stork et al, 2014). Drosophila astrocytes respond to neuronal activity with altered transporter expression and intracellular calcium dynamics (Muthukumar et al, 2014;Stork et al, 2014), they influence CNS synapse number during neural circuit formation (Muthukumar et al, 2014) and modulate locomotor behavior, seizures and olfactory processing (Liu et al, 2014;Rival et al, 2004;Stacey et al, 2010;Stork et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most, if not all neuropil glia (both ensheathing and astrocytelike), are generated from a small number of type II lineages in the posterior brain. Interestingly, the identity of these secondary neuro-glioblasts is different from that of the embryonic neuroblasts that had produced primary glia (Omoto et al 2015 ). Another rich source for secondary glia is the optic lobe (Edwards et al 2012 ).…”
Section: Gliamentioning
confidence: 96%